Рус-Бухоро урушларидаги ҳарбий ҳаракатлар тарихининиг манбаларда ёритилиши (SCIENCE and SOCIETY, 2023)
This article examines the military operations in the Russian-Bukhara wars and their coverage in local sources. Also, in